Theoretical and numerical computation of impact impulse due to frictionless collision experienced by a spent nuclear fuel disposal canister accidentally dropped on the ground - Kwon, Young Joo (Journal of mechanical science and technology, 2016)
This paper presents the theoretical and numerical computation of the impact impulse occurring due to a frictionless collision between a spent nuclear fuel disposal canister and the ground subject to an accidental drop and impact event. The theoretically computed analytical results are in agreement with the numerically generated results.